2019
DOI: 10.1021/acs.jpcb.9b07341
|View full text |Cite
|
Sign up to set email alerts
|

DNA Integration with Silver and Gold Nanoparticles: Enhancement of DNA Optical Anisotropy

Abstract: DNA integration with silver and gold nanoparticles was carried out by the chemical reduction of silver and gold ions after the formation of their complexes with high molecular DNA in solution. It is shown that, for a good association of DNA with nanoparticles, the ions of silver and gold should be linked with DNA bases rather strongly. The proposed model of gold interaction with DNA is the coordination of gold to N7 guanine in a major groove followed by the transformation of the GC pair to Hoogsteen’s type pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
(59 reference statements)
1
3
0
Order By: Relevance
“…DNA2-Ag (Figure E) with an average diameter of around 10 nm was observed by TEM. Through the UV spectra (Figure F), the two characteristic peaks that appeared in curve b indicated that we obtained DNA2-Ag, which were consistent with previous reports. , …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…DNA2-Ag (Figure E) with an average diameter of around 10 nm was observed by TEM. Through the UV spectra (Figure F), the two characteristic peaks that appeared in curve b indicated that we obtained DNA2-Ag, which were consistent with previous reports. , …”
Section: Resultssupporting
confidence: 91%
“…Through the UV spectra (Figure 1F), the two characteristic peaks that appeared in curve b indicated that we obtained DNA2-Ag, which were consistent with previous reports. 40,41 Release of DNA3-ROX in Automatic Cascade Operations. To investigate whether DNA3 hairpins could be successfully released in a cascade reaction in the existence of telomerase and dNTPs, we had encapsulated DNA3-ROX in FOMNs (Scheme 1A).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We used the same procedures for preparing the silver and gold nanoparticles as described in articles [7,28]. The following composition of reagents was used for the synthesis of palladium nanoparticles in solution: the concentration of K 2 PdCl 4 was [K 2 PdCl 4 ] = 0.25 mM, and the concentration of reducing agent NaBH 4 was 1.5 mM.…”
Section: Synthesis Of Metal Nanoparticlesmentioning
confidence: 99%
“…This technique of DNA metallization might find use in the DNA-assisted fabrication of nanostructures. Kasyanenko et al [ 79 ] demonstrated the formation of complexes with nitrogen bases on DNA by using Ag + and Au 3+ , and reduced these ions into Ag NPs (2–10 nm) and Au NPs (3–6 nm), but the NPs were not constructed into NWs. Ganguly et al [ 53 ] incorporated borane phosphate DNA onto CNTs; when Ag + , Au 3+ , or Pd 2+ was incubated with the constructs they were reduced into NPs because of the incorporated reducing equivalents.…”
Section: Metallization Of Dna Templatesmentioning
confidence: 99%